Comparison of CT scan and intraoperative findings of cervical lymph node metastasis in oral squamous cell carcinoma with post-operative histopathology - Sharma, Raghav; Agarwal, Navneet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: In oral cancer are 90% are squamous cell carcinomas (SCC) and lymphatic metastasis influences prognosis .With help of contrast CT scan finding done preoperatively and intraoperative finding during neck dissection we tried to generate a scoring system by which we can predict cervical lymph nodes metastasis systematically. Methods: Biopsy proven oral SCC cases underwent surgery between May 2012 to December 2018. Contrast enhanced computerized tomography (CECT) neck, intraoperative finding and post operative HPR (histopathology) were compared for the largest size node in the neck. Sensitivity, specificity, PPV, NPV and accuracy were calculated by using the hpr findings in the neck dissection specimen as control. Out of 68 cases, supraomohyoid neck dissection was done in 16 cases and radical neck dissection in 52 cases. Scores were put in Open Epi screening test software. Best cut off point was calculated using Youden Index. Results: Best cut off score (using Youden index and ROC curve) for CT scan was >1 out of 7 features (size >10 mm, central necrosis of lymph node, matting of lymph node, shape, extracapsular spread, vascular invasion, central hypodensity). Best cut off for intraoperative palpation was ≥3 out of 4 features (size, feel on palpation, adherence to surrounding structure, shape). Conclusions: Intraoperative findings can change the extent of surgery for being high sensitive and specific as compared to CT scan which is high sensitive but low specificity. A scoring system can be generated preoperative and intraoperatively to predict a node being malignant or not.